Expression of various insulin-like growth factor-1 mRNA isoforms in colorectal cancer - Kasprzak, Aldona; Szaflarski, Witold; Szmeja, Jacek; Andrzejewska, Małgorzata; Przybyszewska, Wiesława; Koczorowska, Maria; Drews, Michał; Kaczmarek, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Several epidemiological studies have attempted to demonstrate a relationship between increased serum level of insulin-like growth factor 1 (IGF-1) and an augmented risk of developing colorectal cancers (CRC). The human IGF-1 gene is composed of 6 exons and demonstrated expression of 6 different splice variants (isoforms) of mRNA (IA, IB, IC, IIA, IIB and IIC).The aim of the study was to evaluate the expression of different isoforms of IGF-1 mRNA in CRC and normal colon tissue. Material and methods : 13 paired tissue specimens (colorectal tumor and non-tumor tissues) were analyzed using both quantitative polymerase chain reaction (PCR) and immunocytochemistry methods (IHC). The expression of classes I and II and variants A, B, C of IGF-1 mRNA were measured. Results : In CRC higher amounts of IGF-1  class II mRNA than class I mRNA were detected. Among A, B, C isoforms, A variant of IGF-1 mRNA prevailed. The amounts of IGF-1 class I and class II mRNAs and of IGF-1 variant B mRNA were lowered in CRC as compared to the control. In CRC significant correlations were detected between reciprocal expression of class I and class II as well as between I and II isoforms and A, B and C. Conclusions : Expression of IGF-1 mRNA isoforms differs between normal and CRC tissues. Even if all isoforms of IGF-1 mRNA manifested correlations with each other in tissues of CRC, expression of all transcripts (except that of isoform A) was significantly decreased as compared to the control.